Evaluasi Implementasi Kebijakan Pendidikan Inklusi - Lukitasari, Sasadara Wahyu; Sulasmono, Bambang Suteng; Iriani, Ade (Universitas Kristen Satya Wacana, 2017)
The purpose of this study is to evaluate the implementation of inclusive education policy in Salatiga City. This study used a qualitative evaluative approach to the research subject of Dinas Pendidikan and inclusion schools in Salatiga. In-depth interviews, document studies, and observations were used to collect data and then analyzed using an Edwards III implementation model that looked at communication, resource, disposition, and bureaucratic structure. The results showed that the implementation of inclusive education policy in Salatiga is considered good, that is the achievement of 65%. Communication is an aspect that requires a lot of improvement, as well as the bureaucratic structure and disposition that is still not a good implementation. While the best aspect is the resources. The impact of this policy is evident from the increasing number of students in regular schools from year to year and the reduced discrimination experienced by ABK students by peers, teachers and the community.